The Impact of the Implementation Total Quality Management on the Performance of Construction Projects A case Study on the Association of Investors in the Housing Sector in Jordan - Alzu'bi, Feras Ali Khalefh; Al-Jaghbeer, Mohammed Ismail (Journal of Economic, Administrative and Legal Sciences, 2019)
The aim of this study was to test the impact of application of TQM on performance of construction projects carried out by the Association of Investors in Housing Sector in Jordan where the descriptive analytical approach and questionnaire methodology were used to gather information. The sample of this study was composed of (3600) investors in housing sector. The random sample method was used to determine sample size which was (346). Questionnaire was distributed and retrieved from investors , the valid ones for analysis was (297) which represent 88% of sample size, which were analyzed by using a set of statistical methods such as linear and multiple regression, and other methods contained in the Social Science Statistical Package. The study showed positive effect of the independent variable (total quality management) on the dependent variable (performance of the construction projects) dimensions represented by (cost, quality, and time) and this effect could be ranked in descending order as follows: time, cost, quality. The study showed also that the dimensions of the independent variable (TQM) in its positive effect on the dependent variable (performance of construction projects) could be ranked in descending order as follows: staff empowerment, continuous improvement, customer focus, leadership, operations management and supplier management. The study recommended the Association of investors in the housing sector in Jordan to clear the positive effect of TQM on project efficiency by indicating its positive impact on time, cost and quality of projects and to urge them to improve level of application of TQM in their projects.It recommended also conducting similar studies on other sectors, such as industrial and services sectors, to show their effects on them and compare results between different sectors to reach common points between them.